2011
DOI: 10.1111/j.1399-0004.2011.01776.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolated and syndromic forms of congenital anosmia

Abstract: Loss of smell (anosmia) is common in the general population and the frequency increases with age. A much smaller group have no memory of ever being able to smell and are classified as having isolated congenital anosmia (ICA). Families are rare, and tend to present in a dominant inheritance pattern. Despite a strong degree of heritability, no human disease-causing mutations have been identified. Anosmia is part of the clinical spectrum in various diseases, as seen in Kallmann syndrome, various ciliopathies and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
78
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 83 publications
(122 reference statements)
0
78
0
2
Order By: Relevance
“…The most common form is acquired anosmia related to trauma or upper respiratory tract infection (2). An association with neurodegenerative disorders has been reported (2).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most common form is acquired anosmia related to trauma or upper respiratory tract infection (2). An association with neurodegenerative disorders has been reported (2).…”
Section: Introductionmentioning
confidence: 99%
“…The most common form is acquired anosmia related to trauma or upper respiratory tract infection (2). An association with neurodegenerative disorders has been reported (2). A small minority of patients with anosmia are classified as having congenital anosmia (CA), defined as absent recall of olfactory sensations since birth in the absence of any disease known to cause anosmia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Behavioural studies investigating taste sensitivity in congenital olfactory im paired subjects are scarce, given the low prevalence of the condition, which affects only 0.05% of the general population (Karstensen and Tommerup, 2011). Hasan et al (2007) found similar electrogustometric thresholds in patients with congenital anosmia due to Kallman syndrome and healthy normosmic subjects, although this negative result could easily be attributed to their low samples size of only four subjects per group.…”
Section: Behavioural Studiesmentioning
confidence: 95%
“…Isolated congenital anosmia (OMIM 107200) is a rare condition where patients have no recollection of ever being able to smell 1 . Unlike syndromic forms of anosmia, ICA patients have no additional symptoms, and no other underlying disease-causing condition can be identified 1 .…”
Section: Introductionmentioning
confidence: 99%